DAMPAK GREEN ACCOUNTING DAN KINERJA LINGKUNGAN TERHADAP PROFITABILITAS PERUSAHAAN YANG TERDAFTAR DALAM INDEKS SRI-KEHATI TAHUN 2022-2024 - Elda Legia S. Pasaribu; Lorina Siregar Sudjiman; Meidy Lieke Karundeng (ITB AAS Indonesia Surakarta, 2026)
By using green accounting practices, a business shows that it is serious about reducing its environmental effect. Companies included in the SRI-KEHATI index will have their 2022-2024 profitability impacted by green accounting and environmental performance, according to this analysis. Environmental reports prepared in accordance with the GRI criteria for 2021, environmental performance measured by PROPER, and return on assets (ROA) are the three main components that make up green accounting. With the help of Eviews 12 software, we performed data processing utilizing panel regression analysis, which included statistical testing, model selection, and hypothesis verification. This method relied on panel data regression using a Random Effect Model (REM). The results indicate that Green Accounting significantly and negatively affects ROA (p=0.0478), whereas Environmental Performance does not (p=0.6213). company profitability is not significantly affected by either of them at the same time (F=2.336540; p=0.130810). With an R2 of 0,1358, we can see that our model adequately accounts for 13.58% of the variation in profitability. As a result, there has been no progress in integrating sustainability techniques. Keywords: Green Accounting, Environmental Performance, Profitability.